PUBLIC RELATIONS COMMUNICATION STRATEGY IN EXCELLENT SERVICE THROUGH LIBRARY TOUR ACTIVITIES AT THE UNIVERSITY OF INDONESIA LIBRARY - Laura, Donna Wahyuni; Samosir, Fransiska Timoria; Widiyarti, Diyas (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Library tour activities at the UI Library are carried out by Public Relations under the Head of the General Administration and Facilities Coordinator. The UI Library has one public relations staff. To meet various needs, the Library must continue to improve the quality of its offerings, therefore public relations plays an important role in the running of the library tour. The purpose of the library tour is to make Library services better by providing a good experience to its participants, but there is still little research that explicitly looks at how public relations communication strategies or tactics are successful in providing the best possible service during a library tour. This study aims to describe the author's findings regarding public relations communication strategies in excellent service. The type of qualitative research is a descriptive approach. The informants in this study were public relations and additional informants who were library tour participants. The results of this study, first public relations created a route design strategy, second public relations created a human resource design, third public relations created an interactive method in the form of questions and answers during the library tour, fourth public relations published news of activities through Instagram and the website. On Instagram, public relations also published video testimonials, messages and impressions of participants after the activity took place. Furthermore, the form of excellent service provided by public relations, namely Friendliness, Speed, Truth, empathy, and very impressive, in the sense that the service gives a good impression of the Library. The form of excellent service can also be proven by the return of related agencies for library tours which indicates that the service provided is good, because the information provided can be conveyed well by the participants of the relevant agencies. The significance of this study lies in its efforts to fill the literature gap related to public relations communication strategies in excellent service in academic library environments. This study is expected to provide theoretical contributions in the field of organizational communication and provide practical input for other libraries that want to develop similar programs.